A study of tubal ectopic pregnancy based on the histopathology of fallopian tubes in the age group of 20-35 years - Rudradev Meyur; Dr. Anirban Sadhu; Hironmoy Mondal; Rupkamal Das (International Journal of Medical Research and Review, 2020)
Purpose: Ectopic pregnancy is a life-threatening condition for the mother. Disruptions of the fallopian tube are considered to be important in its pathogenesis. The present study was conducted to observe the histopathology of this dreaded disease which could lead to the development of suitable remedies.Methods: Cases diagnosed with ectopic gestation in the fallopian tube who subsequently underwent salpingectomy were considered for the study. Histopathology of sections from the affected fallopian tubes was studied under the light microscope after staining with H and E.Results: Most cases presented with amenorrhoea, whereas others had dysmenorrhoea, menorrhagia, and menometrorrhagia. Histopathologic findings included the presence of salpingitis (acute and chronic), calcification, sclerosed vessel and.Conclusion: Past history of inflammatory diseases, especially PID plays an important role in the subsequent development of ectopic pregnancy. Its prevention and treatment can lead to a decrease in the incidence of ectopic pregnancy.